2013
DOI: 10.5586/asbp.2013.006
|View full text |Cite
|
Sign up to set email alerts
|

Variation and genetic structure of Serratula lycopifolia populations (Vill.) Kern. (Asteraceae) in Poland and adjacent regions

Abstract: AFLPs were used to analyze the genetic variability of Serratula lycopifolia, one of the rarest plant species in Central and Western Europe, in six populations from the Wyżyna Małopolska upland (Poland), White Carpathian Mts (Slovakia and Czech Republic) and Podolian Upland (Ukraine). The results of polymorphism, PCoA and neighbor-net analyzes showed similar and relatively low genetic variation and high genetic similarity of individuals within each Polish population but there were differences between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…These results once more confirm high genetic variability among individual plants of H. italicum in the wild population. High genetic variability in wild populations is common in cross-pollinating plants from family Asteraceae, such as Tanacetum vulgare, Tanacetum cinerariifolium, Senecio vulgaris, Chamomilla recutita, and Serratula lycopifolia (Cieslak, 2013;Ebadi, Eftekharian, 2021;Grdiša et al, 2014;Mežaka et al, Wolf et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These results once more confirm high genetic variability among individual plants of H. italicum in the wild population. High genetic variability in wild populations is common in cross-pollinating plants from family Asteraceae, such as Tanacetum vulgare, Tanacetum cinerariifolium, Senecio vulgaris, Chamomilla recutita, and Serratula lycopifolia (Cieslak, 2013;Ebadi, Eftekharian, 2021;Grdiša et al, 2014;Mežaka et al, Wolf et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of the Pannonian Basin as a refugium for certain steppe plants have already been suggested 18 , 39 , 40 . Although numerous examples of phylogeographic analysis of Ponto-Pannonian steppe species are known in the literature 41 – 45 , most of these focus their sampling on a smaller part of the whole distribution area, which may undermine phylogeographic reconstruction of the analysed species 42 , 46 . Therefore, we must be cautious in comparing our phylogeographic results with similar results on other steppe species, but the general acceptance of the presence of a steppe refugium in the western part of the area for certain steppe species forecast similar colonisation patterns for—at least some—steppe species: from the west to the east, from the current periphery to the eastern zonal range (“centre”).…”
Section: Discussionmentioning
confidence: 99%
“…While gene flow could affect the increasing level of genetic variation of the Allium populations, it probably does not occur because of the long geographical distance. This process is more probable between the populations in the Karkonosze Mts, where plants are distributed over a smaller area and pollinators can neutralize the negative effect of genetic drift, which can lead to a reduced genetic variation [47,48]. The results of STRUCTURE analysis indicated that some specimens from the Allium populations contained mixed or different genotypes.…”
Section: Discussionmentioning
confidence: 99%